Design of 100nm single-electron transistor (SET) by 2D TCAD simulation - Amiza, Rasmi; Uda, Hashim; Awang Mat, Abd F (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org